Wild plants consumed as recreational teas by ranchers in Baja California Sur, Mexico - Pío-León, Juan Fernando; Nieto-Garibay, Alejandra; León-de la Luz, José Luís; Delgado Vargas, Francisco; Vega-Aviña, Rito; Ortega-Rubio, Alfredo (Instituto de Ecología, A.C., 2018)
Background and Aims: Recreational teas are herbal beverages prepared by infusion/boiling, consumed in a social or food context, generally considered healthy and with medicinal uses but without being the unique purpose of consumption. In Mexico, recreational teas are not commonly mentioned in ethnobotanical studies. This research describes the ethnobotanical uses, phenolics content and antioxidant activity of wild plants used to prepare recreational teas in two ranch communities in Baja California Sur, Mexico: the Sierra La Laguna Biosphere Reserve and San Blas-Cacachilas.Methods: Ethnobotanical information was obtained through semi-structured surveys and stays with the ranchers of both communities. The percentage of citations, preferences and cultural value of each species was calculated; moreover, their medicinal uses were described. The phenolic content and antioxidant activity was determined by colorimetric methods, and they were correlated with ethnobotanical parameters.Key results: Twelve taxa of wild plants were recorded as recreational tea material, 11 in Sierra La Laguna and six in San Blas-Las Cacachilas. Damiana (Turnera diffusa) had the highest cultural value (71.2%), followed by margarita (Aloysia barbata) (41.1%) and wild anise (Tagetes filifolia / T. micrantha) (21.5%). The main medicinal uses of the recreational teas were as anti-flu/ antitussives and as general relaxants. The antioxidant content had a negative correlation with the percentage of citations and the preference. The medicinal uses for A. barbata and the peyote fern (Pellaea ternifolia) are described for the first time, and new uses for damiana and cherry (Prunus serotina) are documented.Conclusions: Ranchers from Baja California Sur have a high affinity for the consumption of recreational teas of wild plants, and those used to treat common ailments such as flu/cough or stress are preferred. This is the first ethnobotanical study about recreational teas in Mexico.